Analisis Karakteristik Personal Pejabat Penatausahaan Keuangan Terhadap Etika Penyusunan Laporan Keuangan Satuan Kerja Perangkat Daerah Surakarta - Almaidah, Siti; Sriyanto, Sriyanto; Wijayanti, Handayani Tri (Graduasi: Jurnal Bisnis & Ekonomi, 2014)
The purpose of the study is to examine and analyze the personal characteristics of the financial administration officials on local agency consisting of locus of control, work experience, gender, equity sensitivity to the ethics of the financial statements on local agency in local government of Surakarta. The population was all employees who work in the government accounting functions in Surakarta. The sample selection criteria using exsidental sampling. Alternative hypothesis tested in this study include: there is a difference between financial administration officials with an internal locus of control and financial administration officials with an external locus of control, senior and junior financial administration officials, financial administration officials of men and women, as well as the financial administration officials benevolents category and financial administration officials entitleds against disclosure, cost and benefit, responsibility, misstate, and timeliness of financial reporting on local agency. Testing Â the validity of research data using the Pearson Product Moment. Data reliability was tested using Cronbach Alpha. While this research hypothesis testing using the Mann Whitney U-Test. The results showed there were significant differences on disclosure, cost & benefits, responsibility and punctuality misstate except between financial administration officials on local agency with an internal locus of control and financial administration officials on local agency with an external locus of control. There were noÂ  significant differences between junior and senior financial administration officials on local agency to the disclosure, cost & benefits, misstate and timeliness of preparation, except responsibility. There were no significant differences between financial administration officials on local agency of men and women to disclosure, cost and benefit, responsibility, misstate, and timeliness. Lastly, financial administration officials benevolent and financial administration officials entitled has significant differences on local agency about disclosure, cost and benefit, responsibility, and misstate, except factor timeliness of financial statements.